Comparing Refugee and South African Migrant Enterprise in the Urban Informal Sector (African Human Mobility Review, 2021)
Comparisons between the informal business operations of South Africans andinternational migrants are increasingly common. The conventional wisdom isthat survivalist South Africans are being displaced by entrepreneurial migrantswith a long tradition of informal enterprise. This paper is the first attempt toexplicitly compare the informal enterprises established by refugees and SouthAfrican migrants in urban areas. The paper is based on a comparative analysisof over 2,000 refugee and South African informal enterprises. The stereotypingof refugees in public discourse as undermining and destroying South Africancompetitors is far-removed from the reality. The idea that refugees have acompetitive advantage as experienced entrepreneurs is also clearly fallacious.Refugees are extremely motivated, hard-working and dedicated, and employ anumber of legitimate business strategies to achieve success.